Pharmacy quality alliance measure: adherence to non-warfarin oral anticoagulant medications. (3rd October 2015) - Crivera, Concetta; Nelson, Winnie W.; Bookhart, Brahim; Martin, Silas; Germain, Guillaume; Laliberté, François; Schein, Jeffrey; Lefebvre, Patrick
Abstract: Background: The Pharmacy Quality Alliance (PQA) recently endorsed adherence to non-warfarin anticoagulant agents as a new performance measure, but the Medicare Part D Star Ratings program has not yet adopted the measure. The current study aims to assess the real-world adherence to medication of patients who used non-vitamin-K-antagonist oral anticoagulants (NOACs) based on the PQA's adherence measure. Methods: Healthcare claims from the Humana database during the year of 2013 were analyzed. Patients older than 18 with ≥2 dispensings of NOAC agents, at least 180 days apart between two NOAC dispensings in 2013 (a criterion to include chronic users), with ≥60 days of supply, and ≥180 days of continuous enrollment prior to the index NOAC were identified. The PQA measure on the index therapy was calculated as the percentage of patients who had a proportion of days covered (PDC) ≥0.8 during their follow-up. Results: A total of 9948 NOAC users (rivaroxaban: n = 4194, dabigatran: n = 5489, apixaban: n = 265) were identified. For rivaroxaban users, the proportion of patients with a PDC ≥0.8 (PQA measure) at 75.4% was significantly higher compared to dabigatran users (67.6%; P < 0.001) and higher compared to apixaban users (70.6%; P = 0.076). When allowing switches to other NOAC agents in the PQA measure, rivaroxaban users had a significantly higher PQA measure at 76.9% compared to both dabigatran (72.9%; P < 0.001) and apixaban (71.3%; P = 0.037) users. Multivariate logistic regression analyses corroborated the findings that rivaroxaban had a significantly higher adherence compared to the other NOAC agents. Limitations: Claims data may have contained inaccuracies, possible change in patterns over time, and the impossibility of knowing whether all supplied tablets were taken. Conclusion: Based on the PQA's adherence measure, rivaroxaban users were found to have a higher adherence compared to dabigatran and apixaban users. Healthcare providers may want to consider the impact of anticoagulation selection on their ability to achieve quality metrics.